A ativação da via hippo altera a sinalização do interferon tau e adopocinas em cultivo luteal primário bovino - Feltrin, Suzana Rossato (2024)
The corpus luteum (CL) is responsible for synthesis of progesterone, sustaining endometrial functions, and supporting early embryonic, fetal, and placental development. Maternal recognition of pregnancy is defined as an interaction between the maternal environment and the concept, signaling to the female the need to maintain the pregnancy based on the suspension of Interferon tau (IFNT) by the embryonic trophectoderm. The expression of proteins induced by IFNT during early pregnancy, such as ISG15, has been demonstrated in extrauterine tissues, including the CL. The Hippo signaling pathway is highly conserved across species and has well-defined roles in regulating organ growth, cell division, regularity, and apoptosis in different tissues, especially during embryogenesis and follicular development. Adipose tissue plays an important endocrine function, releasing several hormones called adipokines, which act in reproductive processes such as steroidogenesis, implantation, and embryonic development. Some studies suggest that YAP activity plays a crucial role in the IFNT signaling process and adipokine release. Therefore, the study hypothesizes that the YAP-TEAD interaction is necessary for IFNT signaling in bovine CL cells, in addition to regulating the transcription of adipokine receptors in luteal cells. The general objective of this study was to evaluate the effect of blocking the YAP-TEAD interaction on the expression of ISGs, Hippo pathway target genes, and adipokine receptors. For this purpose, a primary study was conducted on bovine corpus luteum cells, where they were treated with different concentrations of verteporfin (VP), an inhibitor of the YAP-TEAD interaction, and recombinant bovine interferon (roIFNT). Gene expression analysis revealed that treatment with VP at a concentration of 1uM decreased the expression of ISGs (MX1, MX2, OAS1) in luteal cells. The interference of the YAP-TEAD interaction was able to significantly reduce the mRNA levels of target genes of the Hippo pathway (YAP, CTGF, ANKRD1) and genes encoding adipokine receptors (ITGB1). Inhibition of the YAP-TEAD interaction can influence the expression of key genes involved in IFNT signaling and genes encoding adipokine receptors in bovine luteal cells.